1968
DOI: 10.1002/aja.1001220214
|View full text |Cite
|
Sign up to set email alerts
|

Articular and internal remodeling in the human otic capsule

Abstract: A comprehensive histologic study of the human otic capsule is presented demonstrating the interrelations between cartilage, bone, blood vessels and soft tissue throughout life. Remodeling occurs through continual degeneration of chondrocytes within the uncalcified articular surfaces of the stapediovestibular joint and through continual degeneration of cartilage about the cochlea and semicircular canals. Degenerated chondrocytes are removed by macrophages and new endochondral bone forms from adjacent osteogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1971
1971
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…4C). Previous works on decalcified specimen described a development of the trabecular bone without thickening of the inner cortex 4 . However, the evolution of techniques allowed us to clearly visualize the maturation of the otic capsule bone, proceeding through a predominant thickening of the external cortex and bone marrow cavity obliteration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4C). Previous works on decalcified specimen described a development of the trabecular bone without thickening of the inner cortex 4 . However, the evolution of techniques allowed us to clearly visualize the maturation of the otic capsule bone, proceeding through a predominant thickening of the external cortex and bone marrow cavity obliteration.…”
Section: Discussionmentioning
confidence: 99%
“…Different patterns of inner ear developments have been suggested, some advocating a prenatal maturation of the bony labyrinth based on the observation of complete ossification of the surrounding otic capsule by seven months in utero 4 , and others claiming that the temporal bone undergoes further postnatal changes 5 . However, in most previous works, investigations of fetal inner and middle ear ossification in human fetuses were based on histological examination of decalcified temporal bones specimens 6 and/or on three-dimensional (3D) images extrapolated from serial histological slices 7 , which made accurate measurements quite challenging.…”
Section: Introductionmentioning
confidence: 99%
“…But no decrease in the cell population and matricial fibers or proportional changes in the collagen and elaunin fibers were evident in the annular ligament. A study in the literature has reported that remodeling in the cartilage of the SVJ and otic capsule involves absorption by macrophages and replenishment by mesenchymal cells in the annular ligament and lining cells of the labyrinthin (Gussen 1968b). We did not observe massive accumulation of macrophages, fibroclasts or osteoclasts in the vicinity of the annular ligament that would indicate active tissue decomposition in the healthy functional joint containing highly remodeling tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The major etiopathogenetic causes of otosclerosis are considered to be genetic factors, collagen defects, collagen autoimmunity and viral infection (Chole and McKenna, 2001). So far, numerous histopathological studies on the SVJ have been performed (Davies, 1948;Harty, 1953;Brunner, 1954;Wolff and Bellucci, 1956;Gussen, 1968Gussen, , 1969Bolz and Lim, 1972;De Souza et al, 1991;Okumura and Iwai-Liao, 1993;Merchant et al, 2001;Whyte et al, 2002). In the normal SVJ, both the vestibular surface and the rim of the stapedial base are covered with hyaline cartilage.…”
Section: Introductionmentioning
confidence: 97%